Mapping the current development of Arabic stylistics research in Indonesia: A bibliometric analysis - Ulfa, Saila Fadhila; Sari Habib, Dian Puspita; Adha, Alifia Zahratul; Fadhillah, Intifa; Rahmat; Ramadhan, Ilham; Meliyana, Fitria Susan; Alif, Muhtarul; Syahridho, Muhammad Fadhil; Hasibuan, Azhar Ismail; Zain, Luthfi; Nurjanah (Research Journal in Advanced Humanities, 2026)
This study aims to analyze the development of Arabic stylistics research, including those related to the Qur’an in Indonesia and identify trends in research topics published in Indonesian journals accredited by Sinta and indexed by Scopus. The urgency of this research lies in the indication of stagnation in Arabic stylistics studies in Indonesia, where emerging research themes tend to be repetitive and have not shown significant diversity or innovation. This study analyzes previous publications related to Arabic stylistics that have been published in Sinta-accredited and Scopus-indexed journals in Indonesia. Data were collected through Publish or Perish, Google Scholar, Scopus, and Semantic Scholar databases, with source limitations in the form of journals accredited by Sinta 1 to 6 and journals indexed by Scopus within the publication period of 2015–2024. The analysis was conducted using a bibliometric approach. Based on the search results, there are 113 articles related to Arabic stylistics consisting of 112 articles from Sinta journals and 1 article from Scopus journals. Data collection was carried out using Zotero. Data processing was carried out using VOSviewer to obtain data visualization results. Microsoft Excel was used to generate graphical visuals. The results show that research in Arabic stylistics in Indonesian journals experienced fluctuating developments between 2015 and 2024. Three main topic clusters emerged as trending topics: rhetorical stylistics, linguistic stylistics, and literary stylistics. From the visualization of Arabic stylistics research topics, this field is primarily used for theoretical applications and has not yet explored multidisciplinary or interdisciplinary studies.